CENTRAL ASIANS FIGHTING IN SYRIA: THE DANGER OF ISLAMIC STATE RETOURNEES TO CENTRAL ASIA - Alonso Marcos, Antonio (Journal of the Spanish Institute for Strategic Studies, 2018)
On June 29 2016, a Russian, an Uzbek and a Kyrgyz perpetrated a terrorist attack in Istanbul Atatürk Airport. Roughly 3000 people from Central Asian countries have left their homes and joined the ranks of Islamic State (IS) in Syria. IS recruits them throughout the territory of the former Soviet Union and places them on the battlefield. Governments try to halt this flood of people – many of whom are youngsters — however they are not always very successful. Despite these recruits not holding great weight within the IS structure, social media has been quick to show its grave concern on the issue because of the “call effect” it could have. Thus, the jihadist threat in this region is once again at the top of the security agenda of the countries of Central Asia.